Manolito Four-Eyes - Lindo, Elvira, 1962-; Moriarty, Joanne; Urberuaga, Emilio (Tarrytown, NY : Marshall Cavendish Children, 2010)
Recounts the exploits of the irrepressible Manolito as he navigates the world of his small Madrid neighborhood, along with his grandpa, his little brother, and his school friends.
Translation of: Manolito Gafotas.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
Book Links (A.L.A.), January 2009.
Booklist, May 2008.
Keywords: Families -- Spain -- Juvenile fiction; Grandfathers -- Juvenile fiction; Schools -- Juvenile fiction; Family life -- Spain -- Fiction; Grandfathers -- Fiction; Schools -- Fiction; Family life -- Spain -- Fiction; Grandfathers -- Fiction; School stories; Spain -- Juvenile fiction; Spain -- Fiction; Spain -- Fiction